Pastwatch : the redemption of Christopher Columbus - Card, Orson Scott (New York : TOR, 1997)
Taguri, one of a group of scientists and historians living in a post-apocalyptic world, views the past through a machine, TruSite II, and discovers one of the women she is studying can see her, too. The discovery sets off a debate over whether the past can be changed to save the future.
"A Tom Doherty Associates book.".
Includes bibliographical references (p. [399]-402).
Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
Adult
Keywords: Columbus, Christopher -- Fiction; Columbus, Christopher -- Fiction; Time travel -- Fiction; Alternative histories; Fourth dimension -- Fiction; Science fiction; America -- Discovery and exploration -- Spanish -- Fiction; America -- Exploration -- Fiction; Alternative histories; Science fiction